Yield stability studies of soybean (Glycine max (L.) Merrill) under rhizobia inoculation in the savanna region of Nigeria. (15th April 2018) - Tolorunse, Kehinde D.; Gana, Andrew S.; Bala, Abdullahi; Sangodele, Emmanuel A.
Abstract: Soybean ( Glycine max (L.) Merrill) production is expanding into temperate and tropical environments. Yield stability studies under rhizobia inoculation were investigated in 24 soybean genotypes over two successive growing seasons at three agro‐ecological zone of Nigeria, during the 2015–2016 rainy seasons. Treatments were arranged in a split‐plot design and replicated three times. Treatments were 24 soybean genotypes and three levels of rhizobia inoculation. Results indicated that the variation of genotypes and inoculation on percentage emergence, height, number of leaves, number of branches per plant, total biomass yield, above‐ground biomass and seed yield was significant ( p  = .05). The effects of genotypes (G), environment (E) and G × E interactions on seed yield were also significant. Two soybean genotypes (TGx 1989‐45F and TGx 1990‐110FN) were identified as the most promising in relation to yield stability. Of the three locations, Abuja produced the least interaction effects followed by Igabi and may be most appropriate environments for large‐scale soybean production. Appropriate inoculation of soybean with inoculants (LegumeFix and or NoduMax) should be encouraged in farmer's field.